(untitled) (Contemporary Journal of Social Science Review, 2025)
Environmental pollution in Pakistan is a persistent public health and ecological challenge, with severe air, water, and industrial contamination affecting millions. Media framing plays a critical role in shaping public perception, responsibility attribution, and policy discourse. This study investigates episodic versus thematic framing of pollution in Pakistani print and digital media from January 2021 to December 2022, analyzing 600 articles across six newspapers and three digital platforms. Findings reveal a dominant episodic framing, particularly for air pollution, focusing on discrete events such as smog episodes and water contamination incidents. Thematic coverage, emphasizing systemic causes, governance failures, and industrial accountability, accounted for 38% of articles and was more prevalent in digital media. Responsibility attribution varied by frame: episodic coverage emphasized citizen behavior, whereas thematic coverage highlighted government and industrial roles. The study contributes to understanding how media framing shapes public awareness, policy discourse, and advocacy in environmental crises. Recommendations include promoting balanced coverage that integrates episodic alerts with thematic, structural perspectives to enhance societal response and policy interventions.